MP04: rEDirect: safety and compliance of an emergency department diversion protocol for mental health and addictions patients. (May 2019) - Bismah, V.; Prpic, J.; Michaud, S.; Sykes, N.; Amyotte, J.; Myre, P.; Ohle, R.
Abstract : Introduction : Transportation of patients better served at an alternative destinations (diversion) is part of a proposed solution to emergency department (ED) overcrowding. We evaluated the pilot implementation of the "Mental Health and Addiction Triage and Transport Protocol". This is the first Canadian diversion protocol that allows paramedics to transport intoxicated or mental health patients to an alternative facility, bypassing the ED. Our aim was to implement a safe diversion protocol to allow patients to access more appropriate service without transportation to the emergency department.Methods : A retrospective analysis was conducted on patients presenting to EMS with intoxication or psychiatric issues. Study outcomes were protocol compliance, determined through missed protocol opportunities, noncompliance, and protocol failure (presentation to ED within 48 hours of appropriate diversion); and protocol safety, determined through patient morbidity (hospital admission within 48 hours of diversion) and mortality. Data was abstracted from EMS reports, hospital records, and discharge forms from alternative facilities. Data was analyzed qualitatively and quantitatively.Results : From June 1st, 2015 to May 31st, 2016 Greater Sudbury Paramedic Services responded to 1376 calls for mental health or intoxicated patients. 241 (17.5%) met diversion criteria, 158 (12.9%) patients were diverted and 83 (4.6%) met diversion criteria but were transported to the ED. Of the diverted patients 9 (5.6%) represented to the ED <48rs later and were admitted. Of the 158 diversions, 113 (72%) were transported to Withdrawal Management Services (WMS) and 45 (28%) were taken to Crisis Intervention (CI). There was protocol noncompliance in 77 cases, 69 (89.6%) were due to incomplete recording of vital signs; 6 (10.3%) were direct protocol violations of being transferred with vital sings outside the acceptable range.Conclusion : The Mental Health and Addiction Triage and Transport Protocol has the potential to safely divert 1 in 6 mental health or addiction patients to an alternative facility.